(3x-4)(5x+15)=0

Simple and best practice solution for (3x-4)(5x+15)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-4)(5x+15)=0 equation:


Simplifying
(3x + -4)(5x + 15) = 0

Reorder the terms:
(-4 + 3x)(5x + 15) = 0

Reorder the terms:
(-4 + 3x)(15 + 5x) = 0

Multiply (-4 + 3x) * (15 + 5x)
(-4(15 + 5x) + 3x * (15 + 5x)) = 0
((15 * -4 + 5x * -4) + 3x * (15 + 5x)) = 0
((-60 + -20x) + 3x * (15 + 5x)) = 0
(-60 + -20x + (15 * 3x + 5x * 3x)) = 0
(-60 + -20x + (45x + 15x2)) = 0

Combine like terms: -20x + 45x = 25x
(-60 + 25x + 15x2) = 0

Solving
-60 + 25x + 15x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '5'.
5(-12 + 5x + 3x2) = 0

Factor a trinomial.
5((-3 + -1x)(4 + -3x)) = 0

Ignore the factor 5.

Subproblem 1

Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3

Subproblem 2

Set the factor '(4 + -3x)' equal to zero and attempt to solve: Simplifying 4 + -3x = 0 Solving 4 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 0 + -4 -3x = 0 + -4 Combine like terms: 0 + -4 = -4 -3x = -4 Divide each side by '-3'. x = 1.333333333 Simplifying x = 1.333333333

Solution

x = {-3, 1.333333333}

See similar equations:

| -96-58=-1894 | | 3m=7(m+6) | | 11=(-2x+2)+5 | | 38x+16=54 | | 36+3x=12x | | 9w=56+w | | 2x-3x+18=-4x-4 | | 4n+65=93 | | U=48n+210+7n+7 | | 18+2x=6y | | 1x+30=2x | | Y=2/9x-7 | | 1x+54=7x | | 2=10/3z=3z-7/3 | | 1/16a^2-1/25=0 | | a=8+b | | U=6*8n+6*35+7*n+7*1 | | =6*8n+6*35+7*n+7*1 | | x^2-208=0 | | f(a)=4x^2+2x+8 | | 2n+m-7m=-2 | | 5/6=-1/8x | | 1/3x2-4=21 | | 7x^2+6xy-y^2=0 | | 4(x+6)-3x=-2x+2-8 | | 0.7x-33.33=x+7 | | 11a-b+3a-(-7b)= | | w^2-3w-1890=0 | | 12x^2-(4x-3)(3x+1)=-2 | | 4(x-4)+2x=3(x-2)+5 | | 0.75x-33.3=x+7 | | U=23(6)+240 |

Equations solver categories